Development of a Competency Training Model for Elementary School Physical Education Teachers - Parengkuan, Meyke; Sudijandoko, Andun (Faculty of Sport and Health Sciences, 2022)
This study aims to develop the competence of Physical Education teachers at SD Kota Utara Gorontalo, as well as teachers' understanding of learning concepts. View and test the effectiveness of the products produced in increasing the competency of elementary physical education teachers regarding learning concepts in Kota Utara District, Gorontalo City which lead to the 2013 Curriculum Education learning process. The research method used is the research and development model, namely: Model Development, Procedure Development, Product Testing with 17 Physical Education teachers as subjects in North Gorontalo District. The development of understanding competence in the teaching and learning process for physical education for elementary school teachers in the North City District of Gorontalo City can be developed regarding understanding of learning concepts as evidenced by changes in understanding through tests of initial understanding and final understanding during debriefing, as evidenced by the results of an initial understanding score of 5.88% (No Good), 52.94% (Poor), 41.18% (Enough) and the final understanding score obtained a score of 16.7% (Enough), 33.3% (Good), 50% (Very Good). Thus, the percentage increase in the level of development of subject competencies is very good. 4) The competence and ability of the teacher in implementing the Teaching and Learning Process of physical education is very visible, its development after receiving a briefing on the concept of learning is proven in the first trial (small group) and the second trial the improvement is very good and very high.